Profiling of MicroRNAs in Midguts of Plutella xylostella Provides Novel Insights Into the Bacillus thuringiensis Resistance - Yang, Jie; Xu, Xuejiao; Lin, Sujie; Chen, Shiyao; Lin, Guifang; Song, Qisheng; Bai, Jianlin; You, Minsheng; Xie, Miao (Frontiers in Genetics, 2021)
The diamondback moth (DBM), Plutella xylostella, one of the most destructive lepidopteran pests worldwide, has developed field resistance to Bacillus thuringiensis (Bt) Cry toxins. Although miRNAs have been reported to be involved in insect resistance to multiple insecticides, our understanding of their roles in mediating Bt resistance is limited. In this study, we constructed small RNA libraries from midguts of the Cry1Ac-resistant (Cry1S1000) strain and the Cry1Ac-susceptible strain (G88) using a high-throughput sequencing analysis. A total of 437 (76 known and 361 novel miRNAs) were identified, among which 178 miRNAs were classified into 91 miRNA families. Transcripts per million analysis revealed 12 differentially expressed miRNAs between the Cry1S1000 and G88 strains. Specifically, nine miRNAs were down-regulated and three up-regulated in the Cry1S1000 strain compared to the G88 strain. Next, we predicted the potential target genes of these differentially expressed miRNAs and carried out GO and KEGG pathway analyses. We found that the cellular process, metabolism process, membrane and the catalytic activity were the most enriched GO terms and the Hippo, MAPK signaling pathway might be involved in Bt resistance of DBM. In addition, the expression patterns of these miRNAs and their target genes were determined by RT-qPCR, showing that partial miRNAs negatively while others positively correlate with their corresponding target genes. Subsequently, novel-miR-240, one of the differentially expressed miRNAs with inverse correlation with its target genes, was confirmed to interact with Px017590 and Px007885 using dual luciferase reporter assays. Our study highlights the characteristics of differentially expressed miRNAs in midguts of the Cry1S1000 and G88 strains, paving the way for further investigation of miRNA roles in mediating Bt resistance.